Speech act realisation strategies and possible effects of transference by speakers of Khoekhoegowab into English when acquired as a second language. - Uises, Yolanda Hermien (Stellenbosch : Stellenbosch Univesity, 2018)
Thesis (MA)--Stellenbosch University, 2017.